EFFECTIVENESS OF ROLE PLAY IN IMPROVING COMMUNICATION COMPETENCE OF PRESCHOOL CHILDREN - darsan, darsan (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2024)
The purpose of the study was to comprehensively analyse and measure the effectiveness of the role-play method in improving preschool children's communication competence. in the development of social and academic skills, communicating effectively is not just about conveying wishes, but also forms the foundation of complex social interactions helping preschool children to build positive relationships with peers, teachers, and the surrounding environment, Role play is a highly effective method of improving preschool children's communication competence. By integrating this approach into the educational curriculum, educators can provide rich and immersive learning experiences that support children's social, emotional and cognitive developmenThe research methodology used a quasi-experimental approach with a non-equivalent control group design. The research subjects were 25 preschool children who were selected by purposive sampling. The research instruments used included communication competence observation sheets, interview guidelines, and documentation that had been validated by early childhood education experts. Data analysis used paired sample t-test and independent sample t-test statistical tests with a significance level of 5%,, Role play is a highly effective method of improving preschool children's communication competence. By integrating this approach into the educational curriculum, educators can provide rich and immersive learning experiences that support children's social, emotional and cognitive development